Use of waste stone powder to improve performance of problematic soils - A Review. - Sherwany, Jaylan; Kakrasul, Jamal (Anbar Journal of Engineering Sciences, 2023)
Problematic soils, especially clayey soil, are problematic for engineering projects in their natural state because of clay's swell-shrinkage phenomenon. Numerous methods and stabilizer materials have been used to enhance clay's geotechnical properties and make them appropriate for construction. One of the significant methods of stabilization of problematic soil is using waste materials like waste glass, waste stone, waste plastic, etc. Due to the waste stone's consistency reducing water content and increasing the soil's strength, it has been employed in many civil engineering studies. Waste stone is available in various forms, including waste stone powder (WSP). WSP is produced by blasting tunnels or cutting huge stone blocks. Hence, the main aim of this study is to review the influence of WSP on improving the geotechnical properties of problematic soils treated with WSP, for this purpose, the treated problematic soils with various percentages of WSP are compared with natural soils. This study evaluates physical properties (i.e., Index properties, linear shrinkage/swelling, optimum moisture content, and maximum dry density) and mechanical properties (i.e., unconfined compressive strength and California bearing ratio). Also, the effect of WSP on decreasing the thickness of pavement layers was reviewed